The Rites of Passage of Nina Sayers in Darren Aronofsky’s Black Swan - Della K. Soselisa; Jenny M. Djundjung (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study aims to discuss Nina Sayers’ rites of passage which are portrayed through the use of many kinds of symbols. Each stage of rites of passage is represented by symbols. Thus, I will use the theory of rites of passage to match the symbols with characteristics of each stage and the concept of symbols to analyze the symbols so that the meanings are appropriate to the contexts and able to show the ways Nina Sayers’ rites of passage are symbolized. The analysis shows that each stage of the rites of passage is symbolized by many forms of symbols. It also shows that symbols of rites of passage can actually hold more than one meaning as they can change meanings in each stage of rites of passage. In the end, it can be concluded that symbols in Black Swan have been effectively used to strongly reveal the rites of passage.